Mechanosensitive Gene Regulation by Myocardin-Related Transcription Factors Is Required for Cardiomyocyte Integrity in Load-Induced Ventricular Hypertrophy. Issue 17 (23rd October 2018) - Trembley, Michael A.; Quijada, Pearl; Agullo-Pascual, Esperanza; Tylock, Kevin M.; Colpan, Mert; Dirkx, Ronald A.; Myers, Jason R.; Mickelsen, Deanne M.; de Mesy Bentley, Karen; Rothenberg, Eli; Moravec, Christine S.; Alexis, Jeffrey D.; et al.
Abstract : Background: Hypertrophic cardiomyocyte growth and dysfunction accompany various forms of heart disease. The mechanisms responsible for transcriptional changes that affect cardiac physiology and the transition to heart failure are not well understood. The intercalated disc (ID) is a specialized intercellular junction coupling cardiomyocyte force transmission and propagation of electrical activity. The ID is gaining attention as a mechanosensitive signaling hub and hotspot for causative mutations in cardiomyopathy. Methods: Transmission electron microscopy, confocal microscopy, and single-molecule localization microscopy were used to examine changes in ID structure and protein localization in the murine and human heart. We conducted detailed cardiac functional assessment and transcriptional profiling of mice lacking myocardin-related transcription factor (MRTF)-A and MRTF-B specifically in adult cardiomyocytes to evaluate the role of mechanosensitive regulation of gene expression in load-induced ventricular remodeling. Results: We found that MRTFs localize to IDs in the healthy human heart and accumulate in the nucleus in heart failure. Although mice lacking MRTFs in adult cardiomyocytes display normal cardiac physiology at baseline, pressure overload leads to rapid heart failure characterized by sarcomere disarray, ID disintegration, chamber dilation and wall thinning, cardiac functional decline, and partially penetrant acute lethality. Transcriptional profiling reveals a program of actin cytoskeleton and cardiomyocyte adhesion genes driven by MRTFs during pressure overload. Indeed, conspicuous remodeling of gap junctions at IDs identified by single-molecule localization microscopy may partially stem from a reduction in Mapre1 expression, which we show is a direct mechanosensitive MRTF target. Conclusions: Our study describes a novel paradigm in which MRTFs control an acute mechanosensitive signaling circuit that coordinates cross-talk between the actin and microtubule cytoskeleton and maintains ID integrity and cardiomyocyte homeostasis in heart disease. Abstract : Supplemental Digital Content is available in the text.